THE ANALYSIS OF ENGLISH TEXTBOOK USED IN THE FIRST GRADE OF SENIOR HIGH SCHOOL BASED ON CURRICULUM 2013 - Wita Nurhikmah and Tiarnita Maria Sarjani Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
The objectives of this study were (1) to analyze feasibility of content (2) to analyze feasibility of presentation in the English Textbook “Bahasa Inggris untuk SMA/MA/SMK Kelas X” according to Curriculum 2013. This study used descriptive qualitative. The data collected for this study were from “Bahasa Inggris untuk SMA/MA/SMK Kelas X” published by Yrama Widya with the writer Otong Setiawan Dj. There are 12 chapters within this textbook and the writer determined to study 6 out of 12 chapters as the sample for the whole book. The results of this study were (1) the feasibility of content in English Textbook “Bahasa Inggris untuk SMA/MA/SMK Kelas X” according to Curriculum 2013 with percentage 89.58%. (2) the feasibility of Presentation in English Textbook “Bahasa Inggris untuk SMA/MA/SMK Kelas X” according to Curriculum 2013 with percentage 88.88%. (3) KD and KI in this textbook also according to Curriculum 2013.Therefore, it can be concluded that English Textbook “Bahasa Inggris untuk SMA-MA/SMK Kelas X” published by Yrama Widya, in terms of feasibility of content and feasibility of presentation, was good to be used in the first grade of senior high school using curriculum 2013.